Inherited bleeding disorders in women - Lee, Christine A.; Kadir, Rezan A.; Kouides, Peter A. (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2009)
The first book with a holistic approach to all aspects of care for women with inherited bleeding disorders. Inherited bleeding disorders have an adverse effect on the quality of life of afflicted women. Management of these women and their conditions is challenging and close collaboration between professionals in different specialties is needed. International experts and leaders of clinical research including hematologists, obstetrician-gynecologists, an anesthetist and those involved in patient advocacy show you how in this practical guide for clinicians. This book covers the gynecological and obstetric issues for: carriers of hemophilia; women with von Willebrand's disease; rare bleeding disorders and, inherited platelet disorders. This book includes recent advances in the field and explores areas for future research. The women's perspective and the efforts of advocacy groups are also discussed in the final chapter. These features make this book a unique, comprehensive and multi-disciplinary resource.
Approach to the patient with an inherited bleeding disorder / Peter A. Kouides and Clare Philipp -- Physiology of menstruation and menorrhagia / M{uA86E}s Edlund -- Haemophilia A and hemophilia B / Christine A. Lee -- von Willebrand's disease / Peter A. Kouides -- Rare bleeding disorders / Flora Pevyandi -- Platelet disorders / Claire Philipp -- Gynecology / Rezan A. Kadir -- Genetic and laboratory diagnosis / Edward Tuddenham -- Antenatal diagnosis / Claudia Chi and Rezan A. Kadir -- Obstetric management / Claudia Chi and Rezan A. Kadir -- Analgesia and anaesthesia for pregnant women with inherited bleeding disorders / Claudia Chi, Adrian England, and Rezan A. Kadir -- The newborn / H. Marikje van den Berg and Rochelle Winikoff -- Advocacy for women with bleeding disorders / Rezan A. Kadir [and others].
Includes bibliographical references and index.
Print version record.
Keywords: Blood coagulation disorders; Women -- Diseases; Blood coagulation disorders in pregnancy; Blood Coagulation Disorders, Inherited; Women's Health; Blood coagulation disorders; Blood coagulation disorders in pregnancy; Women -- Diseases; Electronic books